1998
DOI: 10.1023/a:1005007602986
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The anthelmintic efficacy of benzimidazoles (albendazole, fenbendazole and oxfendazole), levamisole, oral ivermectin and closantel was evaluated on a farm in Kenya using faecal egg count reduction test, larval cultures and a controlled slaughter trial. The results of this study indicated simultaneous resistance of Haemonchus contortus against benzimidazoles, levamisole and ivermectin, and of Trichostrongylus colubriformis and Oesophagostomum spp. against levamisole on the same farm. Ivermectin resistance devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In addition to this, difference in genetic predisposition to develop resistance may contribute to the observed difference in resistance between the two species of parasites (Sangster 2001;Coles 2005). This finding agrees with previous reports in which complete susceptibility of O. columbianum to albendazole was observed in farms where the other parasites like Haemonchus and Trichostrongylus were found highly resistant (Waruiru et al 1998;Wanyangu et al 1996).…”
Section: Fec Reduction Tests Conducted In Both Goats Andsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition to this, difference in genetic predisposition to develop resistance may contribute to the observed difference in resistance between the two species of parasites (Sangster 2001;Coles 2005). This finding agrees with previous reports in which complete susceptibility of O. columbianum to albendazole was observed in farms where the other parasites like Haemonchus and Trichostrongylus were found highly resistant (Waruiru et al 1998;Wanyangu et al 1996).…”
Section: Fec Reduction Tests Conducted In Both Goats Andsupporting
confidence: 91%
“…This is in agreement with the observation of Ademe (2003) that H. contortus caused the death of goats a week after treatment with albendazole in the farm where strain of the suspected parasites in the present experiment were isolated. H. contortus has been reported to be the main species involved in drug resistance in different countries (Borgsteede et al 1996;Waruiru et al 1998;Waller 2003). It has also been shown that the problem of anthelmintic resistance is clearly linked to the drenching frequency, the presence of H. contortus and the prevailing type of grazing management (Waller et al 1995).…”
Section: Fec Reduction Tests Conducted In Both Goats Andmentioning
confidence: 99%
See 1 more Smart Citation